Iron K alpha line of Kerr black holes with scalar hair - Ni, Yueying (2016)
Recently, a family of hairy black holes in 4-dimensional Einstein gravity minimally coupled to a complex, massive scalar field was discovered [1]. Besides the mass M and spin angular momentum J, these objects are characterized by a Noether charge Q, measuring the amount of scalar hair, which is not associated to a Gauss law and cannot be measured at spatial infinity. Introducing a dimensionless scalar hair parameter q, ranging from 0 to 1, we recover (a subset of) Kerr black holes for q = 0 and a family of rotating boson stars for q = 1. In the present paper, we explore the possibility of measuring q for astrophysical black holes with current and future X-ray missions. We study the iron K alpha line expected in the reflection spectrum of such hairy black holes and we simulate observations with Suzaku and eXTP. As a proof of concept, we point out, by analyzing a sample of hairy black holes, that current observations can already constrain the scalar hair parameter q, because black holes with q close to 1 would have iron lines definitively different from those we observe in the available data. We conclude that a detailed scanning of the full space of solutions, together with data from the future X-ray missions, like eXTP, will be able to put relevant constraints on the astrophysical realization of Kerr black holes with scalar hair.